2016
DOI: 10.1021/acs.analchem.6b03949
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Moisture by Fluorescent OFF-ON Sensor in Organic Solvents and Raw Food Products

Abstract: Copper complex based on a new class of fluorescence OFF-ON sensor 1.Cu has been reported for the detection of trace amounts of water in various organic solvents such as CHOH, THF, CHCN, and acetone by means of fluorescence emission intensity. The probe is highly responsive to water in THF (DL = 0.003 wt %). The dissociation of copper from probe 1.Cu in the presence of water is responsible for the fluorescence change and it was confirmed by electrospray ionization-mass spectrometry (ESI-MS), proton nuclear magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(39 citation statements)
references
References 23 publications
1
37
1
Order By: Relevance
“…The limit of detection values [defined as LOD = (3.3 Â SD)/K SV , 27 where K SV is the Stern-Volmer constant] were 0.025% for the Eu 3+ complex of 1 and 0.019% for the Tb 3+ complex of 3. These values are comparable to those of the most sensitive water sensors described up to date (in the range of 0.002-0.2% for CH 3 CN), 2,28 including some lanthanide complexes and metal-organic frameworks (MOFs, in the range of 0.003-0.05%). 12,29,30 In conclusion, we have presented herein two new families of lanthanide antennas that, interestingly, are among the smallest lanthanide antennas able to coordinate these cations, sensitizing their luminescence.…”
supporting
confidence: 80%
“…The limit of detection values [defined as LOD = (3.3 Â SD)/K SV , 27 where K SV is the Stern-Volmer constant] were 0.025% for the Eu 3+ complex of 1 and 0.019% for the Tb 3+ complex of 3. These values are comparable to those of the most sensitive water sensors described up to date (in the range of 0.002-0.2% for CH 3 CN), 2,28 including some lanthanide complexes and metal-organic frameworks (MOFs, in the range of 0.003-0.05%). 12,29,30 In conclusion, we have presented herein two new families of lanthanide antennas that, interestingly, are among the smallest lanthanide antennas able to coordinate these cations, sensitizing their luminescence.…”
supporting
confidence: 80%
“…Therefore, the optical properties should be sensitive to water molecules and variable depending on the water content. Several strategies have been demonstrated to meet the requirement, such as intramolecular charge transfer (ICT), [5][6][7][8][9] excited state intramolecular proton transfer (ESIPT), [9][10][11] photo-induced electron transfer (PET), [12][13][14][15][16][17][18] aggregation-induced emission (AIE), 7,29,30 decoloration of hydrogen-bonding photochromic dyes, 31 and other water-triggered mechanisms. [19][20][21][22][23][24][25][26][27][28] Generally, in each system, there is a specic range of water concentration available for detection; AIE is observed in high water concentrations, 7,29,30 whereas other systems exhibit optical changes in a relatively low concentration range.…”
Section: Introductionmentioning
confidence: 99%
“…42 For example, Amilan Jose et al reported the detection of water in various organic solvents, such as methanol, tetrahydrofuran (THF), acetonitrile, and acetone, using uorescence emission intensity in the presence of a Cu complex probe. 43 The luminescence properties of complex 1 dissolved in acetonitrile were studied at room temperature. It was found that 1 exhibited an intense emission band at l em ¼ 650 nm (l ex ¼ 267 nm).…”
Section: Fluorescence Sensing Propertiesmentioning
confidence: 99%